Label free glucose electrochemical biosensor based on poly(3,4-ethylenedioxy thiophene): polystyrene sulfonate/titanium carbide/graphene quantum dots - Mohd Nashruddin, Siti Nur Ashakirin; Abdullah, Jaafar; Mohammad Haniff, Muhammad Aniq Shazni; Mat Zaid, Mohd Hazani; Ooi, Poh Choon; Mohd Razip Wee, Mohd Farhanulhakim (MDPI AG, 2021)
The electrochemical biosensor devices based on enzymes for monitoring biochemical substances are still considered attractive. We investigated the immobilization of glucose oxidase (GOx) on a new composite nanomaterial poly(3,4-ethylenedioxythiophene): polystyrene sulfonate (PEDOT:PSS)/titanium carbide,(Ti3C2)/graphene quantum dots(GQD) modified screen-printed carbon electrode (SPCE) for glucose sensing. The characterization and electrochemical behavior of PEDOT:PSS/Ti3C2/GQD towards the electrocatalytic oxidation of GOx was analyzed by FTIR, XPS, SEM, cyclic voltammetry (CV), and differential pulse voltammetry (DPV). This composite nanomaterial was found to tend to increase the electrochemical behavior and led to a higher peak current of 100.17 µA compared to 82.01 µA and 95.04 µA for PEDOT:PSS and PEDOT:PSS/Ti3C2 alone. Moreover, the detection results demonstrated that the fabricated biosensor had a linear voltammetry response in the glucose concentration range 0–500 µM with a relatively sensitivity of 21.64 µAmM−1cm−2 and a detection limit of 65 µM (S/N = 3), with good stability and selectivity. This finding could be useful as applicable guidance for the modification screen printed carbon (SPCE) electrodes focused on composite PEDOT:PSS/Ti3C2/GQD for efficient detection using an enzyme-based biosensor.